Internalizing the value of Mahabbah in the implementation of the Child-Friendly School (CFS) program at the State Islamic Junior High School in Banda Aceh - Junaidi IB; Syamsul Rijal; Silahuddin Silahuddin; Nurmahni Harahap; Maria Ulfa; Suharman Suharman (Dirasah International Journal of Islamic Studies, 2026)
This study is motivated by the phenomenon that the implementation of Child-Friendly Schools (CFS) is often reduced to administrative and technical formalities, thereby neglecting the theological substance of compassion (maḥabbah). It aims to analyze the integration of maḥabbah values into CFS policies, examine the internalization process among students, and identify supporting and inhibiting factors along with their overall impact. This research employs a qualitative, multi-site design conducted at four State Islamic Junior High Schools (MTsN) in Banda Aceh. Data were collected through participant observation, in-depth interviews, and documentation, and analyzed using the Miles, Huberman, and Saldaña model. The study is grounded in a Three-Tier theoretical framework: Maḥabbah Theology as the grand theory, John Goodlad’s curriculum representation as the middle-range theory, and Nienke Nieveen’s parameters as the applied theory. The findings indicate that: (1) the integration of maḥabbah values has developed into an “inner constitution” of the madrasah, supported by both theological and juridical foundations; (2) the internalization process occurs circularly across Goodlad’s five curriculum levels, culminating in students’ lived experiences, with teachers acting as murabbī who apply al-rifq (gentleness) and syafaqah (tenderness) to create inclusive learning environments; and (3) this process is reinforced by kinship-based social capital despite challenges posed by digital disruption. Empirically, the study demonstrates the formation of moral autonomy, insan kāmil character, and a “zero bullying” ecosystem. It proposes a Dignified CFS Model that integrates Sharia values with modern pedagogy.